The role of climatic models in morphoclimatic risks and their environmental impacts in Babil Governorate - Kadhem, Maher Hamood (Al-Adab Journal, 2022)
The research dealt with the role of climate models and their impact on morpho-climatic risks and their reflection on the environment that were studied according to statistical methods to build (extreme) thermal and rain climatic models, which amounted to (12) recurrences in the study stations. In addition to the natural characteristics of (geology, elevations and slopes, soil, natural vegetation), while the highest amount of water for rain intensity was recorded in (Al-Kifl, Al-Qasim) station, which has an effective role in varying the severity of morpho-climatic risks in the region. The volume of water erosion was estimated according to (Furniah, Gavrilovic) model, and the region was within the category (moderate - high), and its correlation with climatic models reached the strongest with the wet cold model, by (0.72), As for wind erosion, according to (chepil), which is considered very high, and its relationship is stronger with the hot and dry model by (0.80). And building a model for morphoclimatic risks (water erosion risks, sand dune encroachment risks) to determine the degrees of risk for water erosion risks, as high-risk lands occupied (42%), medium-risk (39.7%) and low-risk (18.3%), while the degree of risk of dune encroachment risks sandy sand is high risk (29%), medium risk (53.6%), low risk (17.4%), Then it was evaluated and matched with the map of human uses, as it was found that human activities (agricultural lands, transportation routes, religious and archaeological sites, tourism) have more impact on the risks of water erosion and encroachment of sand dunes that fall within high-risk lands, and the correlation between them is (very strong).